Banana Starch: Properties Illustration and Food Applications—A Review. (14th October 2020) - Dhull, Sanju Bala; Malik, Tanu; Kaur, Ramandeep; Kumar, Pradyuman; Kaushal, Naveet; Singh, Ajay
Abstract: Bananas are a valuable crop that are embedded with various micronutrients. Unripe bananas are of interest because they are used by commercial interests as a source of starch. These starches can be modified to resistant forms to slow digestibility and lower glycemic index. In this context, they are of interest in diabetes, obesity, and cardiovascular disease research. Additionally, there is pharmaceutical interest in modified banana starches in terms of drug delivery and in the textile industry as filler in yarn. Due to the texturizing capacity, mouthfeel, and palatability of banana starches, the beverage, bakery, and confectionery industries have investigated their use for novel formulations. This Review summarizes the properties and applications of banana starches. Abstract : Bananas are a valuable crop that are embedded with various micronutrients. This Review summarizes the properties and applications of banana starches.